How Christian pharmacists can maximize their potentials in healthcare delivery: Adopting the prayer, faith, and action model - Melody Okereke; Kenneth Bitrus David; Ezeofor Ozioma Onyedikachukwu (Health for All Nations, 2020)
In the absence of scientific breakthrough, patients search for solutions beyond science in the quest for good health. This is because spirituality greatly influences therapeutic outcomes and healthcare delivery. Healthcare providers must confront the dual needs of their patients; spiritual and health. Christian pharmacists can have an integral role to play in addressing these needs by means of a specialized focus on Christian faith. In this paper, we propose a Prayer, Faith, and Action Model for pharmacists who desire faith-based healthcare delivery in their professional settings. This model is worth adopting if Christian pharmacists want to maximize their potential in the course of healthcare delivery.